Multi-omics insights into key aroma compound formation during Chinese bayberry wine fermentation by Pichia kluyveri ZFM-0524 - Shuxun Liu; Mingfeng Cao; Yan Zhao; Yufeng Xu; Luan Zhang; Yuling Cai; Qing Gu (International Journal of Food Microbiology, 2026)

Pickering emulsions stabilized by bovine bone gelatin - xanthan gum conjugates: an effective carrier for curcumin encapsulation - Mingfeng Sun; Wenxia Wu; Huanhuan Yang; Mou Zhao; Xiang Zhou; Nengmao Chen; Jingtao Sun; Shiling Lu; Qingling Wang; Juan Dong (Food and Bioproducts Processing, 2026)

Characterization of Pichia pastoris protease and its application in improving the quality and storage stability of dried pork jerky - Ziyuan Zhang; Yuan Huang; Mengning Zhao; Yixin Zhang; Mingfeng Xu; Fangda Sun; Rongrong Yu (Food Chemistry, 2026)

Evaluation of novel probiotic Bacillus candidates from the midgut of gibel carp (Carassius auratus gibelio): effects on fish growth, immunity, and resistance to CyHV-2 infection - Mingming Zhang; Ni Ma; Yaqin Yang; Mingfeng Zhu; Hu Zhang; Zhigang Zhao; Jialin Zhang; Mingzhu Pan; Zhitao Qi; Guo Qiao (Aquaculture International, 2026)

Multivariate data analysis of a severe air pollution event in Shihezi city, China - Feifan Chen; Qing He; Zhujun Zhao; Zhongqi Lu; Mingfeng Yang; Gang Ren; Jin Wang; Hongwei Zhang; Dongliang An; Chunxia Wu (Atmospheric Pollution Research, 2025)

Single-step synthesis of nitrogen and phosphorus co-doped biochar and its application in dye removal: synergistic effects of adsorption and peroxymonosulfate activation - Yixuan Shi; Mingfeng Yin; Dong Liu; Xingrui Gao; Xiao Liu; Tengteng Yang; Zuoping Zhao; Xiaohui Ji; Caibin Zhao; Xianzhao Shao (Environmental Research, 2025)

IRBITs, signaling molecules of great functional diversity - Ying Liu; Xuhui Feng; Han Wu; Tianxiang Gui; Mingfeng Fu; Xudong Luo; Lei Zhao; Li-Ming Chen (Pflügers Archiv - European Journal of Physiology, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Temperature effects on the micro-to-macro mechanical and creep properties of impurity salt rock - Chengxing Zhao; Cheng Lyu; Mingfeng Yang; Yunhui Zhang; Ping Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Prognostic impact of DTA mutation and co-occurring mutations in patients with myelodysplastic syndrome - Min Wang; Ping Chen; Daqi Li; Mingfeng Zhao (Molecular Biology Reports, 2024)

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

Novel benzothiazole-based fluorescent probe for efficient detection of Cu2+/S2− and Zn2+ and its applicability in cell imaging - Linxiu Zhao; Junli Shi; Yongzheng Liu; Mingfeng Han; Shengling Li; Duanlin Cao (Analytica Chimica Acta, 2024)

Self-Buffering system for Cost-Effective production of lactic acid from glucose and xylose using Acid-Tolerant Issatchenkia orientalis - Ye-Gi Lee; Nam Kyu Kang; Chanwoo Kim; Vinh G. Tran; Mingfeng Cao; Yasuo Yoshikuni; Huimin Zhao; Yong-Su Jin (Bioresource Technology, 2024)

Mechanical Characteristics of Red Sandstone Subjected to Freeze–Thaw Cycles and Increasing Amplitude Cyclic Load - Chenyang Zhao; Mingfeng Lei; Chaojun Jia; Guodong Liang; Yuanbo Shi (Rock Mechanics and Rock Engineering, 2024)

Zero-valent iron (nZVI) nanoparticles mediate SlERF1 expression to enhance cadmium stress tolerance in tomato - Ali Anwar; Yudan Wang; Mengqing Chen; Shuaiwei Zhang; Jinmiao Wang; Yunqiang Feng; Yanxu Xue; Mingfeng Zhao; Wei Su; Riyuan Chen; Shiwei Song (Journal of Hazardous Materials, 2024)

A new strategy for enhanced phosphate removal from waters using ferric oxide impregnated biochar - Lili Dong; Yan Li; Xinli Wen; Mingfeng Zhao; Le Zhang; Mengmeng Zhu; Shunli Wan (Chemical Engineering Journal, 2024)

Design of active phase structure with high activity and stability in residue hydrotreating reactions - Yanzi Jia; Anpeng Hu; Dawei Hu; Mingfeng Li; Huifeng Li; Qinghe Yang; Zhiwei Liu; Zhicai Shao; Shuangqin Zeng; Xinqiang Zhao; Yifan Wang (Fuel, 2024)

A novel approach to achieving more efficient production of the mature form of human IL-37 in plants - Yao Zhang; Nadiyah Alqazlan; Zihe Meng; Jingyao Zhao; Nan Liu; Yuxin Zhang; Mingfeng Feng; Shengwu Ma; Aoxue Wang (Transgenic Research, 2023)

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

Experimental and DEM simulations of the mechanical properties of rock under freeze–thaw cycles - Jun Yu; Qiang Zhang; Chaojun Jia; Mingfeng Lei; Chenyang Zhao; Ruifeng Pang; Zong Li; Tao Zeng (Cold Regions Science and Technology, 2023)

Study on the geological adaptability of the arch cover method for shallow-buried large-span metro stations - Mingfeng Lei; Chenyang Zhao; Chaojun Jia; Chenghua Shi (Tunnelling and Underground Space Technology, 2023)

The genesis of the Ni–Cu sulfide mineralization of the carboniferous Haibaotan intrusion, Eastern Tianshan, Central Asian Orogenic Belt - Mingfeng Qiu; Yun Zhao; Chunji Xue; Jia Chen; Xiaoping Ma; Lu Wang; Liang Yu; Yanxiang You (International Journal of Earth Sciences, 2023)

Asymmetric large deformation of tunnel induced by groundwater in carbonaceous shale - Chenyang Zhao; Mingfeng Lei; Chaojun Jia; Keyue Zheng; Yintao Song; Yuanbo Shi (Bulletin of Engineering Geology and the Environment, 2022)

Exudate components exert different influences on microbially mediated C losses in simulated rhizosphere soils of a spruce plantation - Yuanshuang Yuan; Wenqiang Zhao; Juan Xiao; Ziliang Zhang; Mingfeng Qiao; Qing Liu; Huajun Yin (Plant and Soil, 2017)

Impacts of global emissions of CO, NO x , and CH4 on China tropospheric hydroxyl free radicals - Mingfeng Su; Yunping Lin; Xinqiang Fan; Li Peng; Chunsheng Zhao (Advances in Atmospheric Sciences, 2012)

Differentiation of Schisandra chinensis and Schisandra sphenanthera using metabolite profiles based on UPLC-MS and GC-MS - Zhiyong Guo; Aihua Zhao; Tianlu Chen; Guoxiang Xie; Mingmei Zhou; Mingfeng Qiu; Wei Jia (Natural Product Research, 2012)

A high-density intervarietal map of the wheat genome enriched with markers derived from expressed sequence tags - Shulin Xue; Zhengzhi Zhang; Feng Lin; Zhongxin Kong; Yong Cao; Chunjun Li; Hongying Yi; Mingfeng Mei; Huilan Zhu; Jizhong Wu; Haibin Xu; Dongmei Zhao; et al. (Theoretical and Applied Genetics, 2008)